Analysis on unconfined groundwater availability during dry and rainy season using dynamic approach in Ngemplak, Sleman, Yogyakarta, Indonesia - Sadewa Purba Sejati; Riski Edi Prayoga (Universitas Negeri Malang, 2023)
Groundwater is a natural resource with disparity across the different regions throughout time. In comparison to surface water, the groundwater in unconfined aquifers is easily accessible and generally of good quality. Groundwater macro zoning is classified into three, namely water catchment areas, transition areas, and groundwater discharge areas. Based on the macro zoning, previous research has mostly been carried out in catchment areas and discharge areas with a focus on groundwater potential and temporary groundwater conditions. The dynamics of groundwater availability, especially in the water transition zone, has not been studied much, even though the dynamics of groundwater availability in the transition zone plays a vital role for areas in the discharge zone. This study identified the availability of groundwater during rainy and dry seasons in groundwater transition zone. Groundwater availability was assessed through a dynamic discharge approach. The study variables included the hydraulic conductivity of the aquifer, the hydraulic gradient, and the cross-sectional area of the aquifer. Dynamic discharges were analysed during the rainy and dry seasons. The results showed that the availability of groundwater during the rainy season was 4,333,906.1 liters/day and 3,898,850.4 liters/day during the dry season. Based on the calculation of the dynamic discharge (Q), the decrease in the quantity of groundwater is affected by the variable hydraulic gradient (I) and cross-sectional area of the aquifer (A). The numbers of these two variables are smaller during the dry season than the rainy season. The decrease in the quantity of groundwater during the dry season is of course closely related to reduced rainfall which is a source of infiltration and percolation. Reduced rainfall causes the groundwater level to decrease, then technically reduces the groundwater hydraulic gradient (I) and aquifer cross-sectional area variable (A). There was no indication of groundwater scarcity in the study area. This study can serve as a reference related to the application of dynamic discharge theory to assess groundwater availability. Periodic monitoring of groundwater quantity, rainwater harvesting, and intensification of water infiltration wells can be carried out as a recommendation to anticipate problems related to groundwater availability in the study area. This study can serve as a reference related to the application of dynamic discharge theory to assess groundwater availability.